Analisis Gaya Bahasa dalam Teks Kelong Sangkak Rupa Mangkasarak - Yuli Sri Astuti; Idawati Idawati; Asia M (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract. This research is a qualitative dascriptive study that aims to wxamine the analysis of languange stayle in the text pappair Kelong sangkak form mangkasarak by using stylistics (Language Style). The data inthis study are in the form of words, phrases, clauses or sentences in the pappasang kelong from Mangkasarak Text. The date collection techniques used in this study are reading techniques, and note-taking techniques. The results of this study get the types of languange styles, besed on comprataive language styles, namely personification, depersonification, symbolic, simile, association, methaphor and efuisme, affirmation, language style, hyperbole, klimaks, anticlimate. Parallelism, polysedenton, Asidenton, Correction, repetition, litotes. Contradictory language stylr, pradox and peleonasme, satire, language style, sarcasm, and cynicism. The meaning of each pharase, sentence, pappair text describes life in carrying out daily life, in order to stick to the costoms and habibts of the Makassar people.Keywords:  languge style, pappair, text, kelong sangkak form.